BANGKITKAN EKONOMI MASYARAKAT DENGAN PENINGKATAN MANAJEMEN USAHA MASYARAKAT PENGRAJIN MAKANAN SINGKONG PADA MASA PANDEMI COVID 19 - Hamdan Hamdan; Badar Ibnussabil; Mila Anjali; Nining Nurasih; Yesi Petricia; Lasmi Suciati; Abdul Holid; Isti Kharoh (Jurnal Abdimas Bina Bangsa, 2022)
During the Corona Virus pandemic in Indonesia, there are limited knowledge / skills and technology that can be accessed in terms of processing technology for various plant products into snacks or snacks. packaging, labeling is also quality and hygiene, so it has not been able to penetrate the market segment, this greatly affects the community's economy. Consumer demand can be met if the level of production remains continuous and the quality of the processed can be maintained. This aspect is still a fundamental problem by community groups about the technology of developing cassava plant products or other plants.  Innovation Solving this problem can be taken, among others, through the development of skills and business management for the people of Sangiang village in improving the community's economy by providing assistance in empowering science and technology about the development of cassava plant products and other plants to be better and produce many product choices. Departing from the problems of partners, through the community service program, together with students have implemented the KKM-Thematic program in the form of mentoring, counseling and training through improving business management for the sangiang village community. The indicators of the achievement of the intended KKM-Thematic Program products are The production performance of the community of craftsmen Food made from cassava is increasing; Good packaging, taste, processing, marketing open the opportunity to improve the economy of the sangiang village community